Analisis Indeks Kepuasan Masyarakat Terhadap Kualitas Pelayanan Publik Menurut PERMENPAN No 14 Tahun 2017 Pada Kantor Lembang Nonongan Selatan - Devica Devica; Mey Enggane Limbongan (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
The research aim to measure the community satisfaction index as service users and improve the quality of public services. The data was obtained by observing and distributing questionarires to the public using birth certificate processing services with asample of 65 respondents. The types of data used in this research are promary anf secondary data. Data analysys techniques is descriptive quantitative method by calculating the percentage of aech category of answers based on PEMENPAN No 14 of 2017. The result of the research show that the community satisfaction index at the Lembang Nononga Selatan, which can be seen from the 9 indicators in accordance with PERMENPAN No 14of 2017 with the average service quality at the conversion value of the community satisfaction index of 85,475